Comparison of Intermodal Transport of Germany, Russian Federation and China - Manukalova, Diana (2020)
The diploma thesis deals with analyzing and comparing the intermodal transport infrastructure in 3 countries: the Russian Federation, Germany, and China. To answer the research question - does the use of intermodal transport differ within one multinational corporation in different countries - a case study methodology is applied, and intermodal planning in the Anheuser-Busch InBev company is investigated through interviews. It was found that the intermodal systems in the three countries differ from each other, as well as the case company´s intermodal planning. Furthermore, current trends and problems that occur in intermodal transport are discussed, and possible proposals for solving these problems are offered. The last part of the work examines new possibilities and potential use of the North Sea Road in the Arctic due to climate change.